2016
DOI: 10.1017/s2040174416000118
|View full text |Cite
|
Sign up to set email alerts
|

In uterobetamethasone affects 3β-hydroxysteroid dehydrogenase and inhibin-α immunoexpression during testis development

Abstract: Prenatal glucocorticoids, commonly used in women at risk of preterm delivery, can predispose the newborn to disease in later life. Since male reproductive function is likely to reflect testis development during fetal life, we studied the effects of prenatal glucocorticoids on two key intra-testicular factors that play roles in cellular proliferation and differentiation, 3β-hydroxysteroid dehydrogenase (3β-HSD) and inhibin-α. Pregnant sheep (n=42) were treated with betamethasone (0.5 mg/kg) or saline (control) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…For example, betamethasone, a glucocorticoid, is used in women at risk of preterm delivery. Recent studies found that in utero betamethasone exposure can disrupt fetal male reproductive development (Borges et al 2016, Pedrana et al 2016, de Barros et al 2018). Similar investigations have been published recently on caffeine, the anti-diabetic drug, metformin, the antiviral drugs, acyclovir and ganciclovir, the anti-epileptic drug, carbamazepine, the antiandrogen and hair loss drug, finasteride, the cholesterol-reducing drug, simvastatin, and others (Bowman et al 2003, Tartarin et al 2012, Andretta et al 2014, Nihi et al 2014, Ogunwole et al 2015, Veroniki et al 2017, Meyer et al 2018, Beverly et al 2019.…”
Section: Mixturesmentioning
confidence: 99%
“…For example, betamethasone, a glucocorticoid, is used in women at risk of preterm delivery. Recent studies found that in utero betamethasone exposure can disrupt fetal male reproductive development (Borges et al 2016, Pedrana et al 2016, de Barros et al 2018). Similar investigations have been published recently on caffeine, the anti-diabetic drug, metformin, the antiviral drugs, acyclovir and ganciclovir, the anti-epileptic drug, carbamazepine, the antiandrogen and hair loss drug, finasteride, the cholesterol-reducing drug, simvastatin, and others (Bowman et al 2003, Tartarin et al 2012, Andretta et al 2014, Nihi et al 2014, Ogunwole et al 2015, Veroniki et al 2017, Meyer et al 2018, Beverly et al 2019.…”
Section: Mixturesmentioning
confidence: 99%
“…Slides were processed for the detection of immunoreactive IGF-I, inhibin, 3β-HSD, HSF1, and Ki-67 (Table 1) using the streptavidin-biotin-peroxidase protocol, as described previously. 38 In brief, tissue sections were deparaffinized and rehydrated and then underwent heat-induced epitope retrieval; slides were immersed in 0.01-M citrate buffer (pH 6.0) and Tween 20 (5 ml), heated for 5 min (microwave oven), and then washed with distilled water and phosphate-buffered saline (PBS, pH 7.4); endogenous peroxidases were inactivated with 3% hydrogen peroxide (20 min), followed by washing in PBS and incubation with normal rat serum to block non-specific binding proteins; sections were then incubated for 30 min with each primary antibody on different slides (Table 1), for 30 min with biotinylated secondary antibody, and for 30 min with streptavidin-peroxidase enzyme complex (Kit Rabbit Specific HRP/DAB-ABC-Detection IHC, ab 64261; Abcam, Eugene, OR, USA); 3,3 0 diaminobenzidine (DAB) chromogen (30 μl) was added to 1.5-ml DAB substrate, mixed, and incubated for 5 min; testis sections were counterstained with Mayer's hematoxylin, dehydrated, and mounted with Entellan® (Merck, Darmstadt, Germany) and placed under a glass coverslip.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…She has shown that the Leydig cells in the ram fetus contain glucocorticoid receptors, and that receptor density is increased by prenatal glucocorticoid treatment (Pedrana et al, 2008). In addition, prenatal glucocorticoid treatment alters dynamics in the expression of 3ß-hydroxysteroid dehydrogenase, an enzyme involved in testosterone synthesis, and decreases the expression of inhibin-α (Pedrana et al, 2016). These effects accompany a reduction in the proliferation of Leydig cells, but not Sertoli cells (Pedrana et al, 2008(Pedrana et al, , 2016, as well as changes the levels of Caspase, Bcl-2, and Bax, shifting the balance from inhibition to promotion of apoptosis (Pedrana et al, 2008).…”
Section: Dohad and Maternal Stress And In The Ram Lambmentioning
confidence: 99%
“…In addition, prenatal glucocorticoid treatment alters dynamics in the expression of 3ß-hydroxysteroid dehydrogenase, an enzyme involved in testosterone synthesis, and decreases the expression of inhibin-α (Pedrana et al, 2016). These effects accompany a reduction in the proliferation of Leydig cells, but not Sertoli cells (Pedrana et al, 2008(Pedrana et al, , 2016, as well as changes the levels of Caspase, Bcl-2, and Bax, shifting the balance from inhibition to promotion of apoptosis (Pedrana et al, 2008). Therefore, it seems likely that stress in the pregnant ewe will affect the proliferation and differentiation of cells in the developing testis of ram fetuses.…”
Section: Dohad and Maternal Stress And In The Ram Lambmentioning
confidence: 99%